Selected Features of Oral Transmission Preserved in the Mahāvastu - Marciniak, Katarzyna (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2022)
The article lists and describes selected features of oral transmission as preserved in the Mahāvastu – a Buddhist Hybrid Sanskrit biography of the Buddha belonging to the Vinayapitaka of the Mahāsāmghika-Lokottaravādins: the principle of waxing syllables, recurrent formulaic phrases, and repetitions.
Keywords: oral transmission; Mahāvastu; Buddhist narrative literature; the principle of waxing syllables; formulaic expressions; repetitions